Khazanah Living Quran dalam Masyarakat Aceh - Muhammad Ridha (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2021)
The study of the Quran as a systematic effort towards matters related to the social phenomena of the Muslim community that responds to the Qur'an has been described since the time of the Prophet and his Companions. The emerging tradition is that the Quran is used as memorization (Tahfiz), sima '(listening), and study of Tafseer in addition to being an object of learning to various regions in the form of